In vitro evaluation of Resveratrol as a potential pre-exposure prophylactic drug against Trypanosoma cruzi infection - Rodriguez, Matias Exequiel (2022)
Chagas' disease or American trypanosomiasis, caused by Trypanosoma cruzi infection, is an endemic disease in Latin America, which has spread worldwide in the past years. The drugs presently used for treatment have shown limited efficacy due to the appearance of resistant parasites and severe side effects. Some of the most recent studies on anti-parasitic drugs have been focused on protein acetylation, a reversible reaction modulated by Acetyl Transferases (KATs) and Deacetylases (KDACs). We have previously reported the anti-parasite activity of resveratrol (RSV), an activator of KDACs type III (or sirtuins), and showed that this drug can reduce the growth of T. cruzi epimastigotes and the infectivity of trypomastigotes. Since RSV is now widely used in humans due to its beneficial effects as an antioxidant, it has become an attractive candidate as a repurposing drug. In this context, the aim of the present study was to evaluate the ability of this drug to protect three different types of host cells from parasite infection. RSV treatment before parasite infection reduced the percentage of infected cells by 50–70% depending on the cell type. Although the mammalian cell lines tested showed different sensitivity to RSV, apoptosis was not significantly affected, showing that RSV was able to protect cells from infection without the activation of this process. Since autophagy has been described as a key process in parasite invasion, we also monitored this process on host cells pretreated with RSV. The results showed that, at the concentrations and incubation times tested, autophagy was not induced in any of the cell types evaluated. Our results show a partial protective effect of RSV in vitro, which justifies extending studies to an in vivo model to elucidate the mechanism by which this effect occurs.